Characterization of Cold Atmospheric Pressure Argon Plasma in Dielectric Barrier Reactor - Singh, Akhilesh Kumar; Guragain, Rajesh Prakash; Shrestha, Asmita; Chhetri, Ganesh Kuwar; Dhungana, Santosh; Baniya, Hom Bahadur; Subedi, Deepak Prasad; Joshi, Ujjwal Man (Tribhuvan University Journal, 2024)
The cold plasma has been produced, using high voltage and line frequency (0-20 kV, 50Hz ) at atmospheric pressure. In this paper, the generation and characterization of plasma produced with argon gas in dielectric barrier discharge (DBD) reactor system is reported. The characterization of produced plasma has been done by electric and optical means using different techniques like current density method, power balance method, Boltzmann plot method, Stark broadening, line intensity ratio method and Saha-Boltzmann relation. Result reveled that electron density was of the order of 1011 cm-3, 1012 cm-3, 1011 cm-3, 1016 cm-3 and as determined by current density method, power balance method, Saha-Boltzmann relation and stark broadening approach respectively while excitation temperature of electron was estimated to be about 0.92 eV and 0.79 eV as determined by Boltzmann plot method and intensity ratio method respectively. The discharge power and energy consumed per cycle are determined using the Lissajous figure approach. The proper characterization of cold atmospheric pressure plasma (CAPP) is essential for seed treatment, polymer treatment and water treatment.